HISTORY OF TASHKENT CITY TRANSPORT (1946-1991) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article examines the history of public transport, the development of the urban transport system in Tashkent from 1946 to 1991, approaches to analyzing changes in the network of transport routes, technical descriptions of vehicles and the level of Service.